Pesantren and Mother Tongue: Madurese Language Maintenance Among Santri at Al-Hikam Bangkalan - ZA, Dede Rosyadi; Silviana, Diah; Zulkhaeriyah, Zulkhaeriyah; Hasan, Amalia (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2025)
The Madurese language is slowly shifting because many young people prefer Indonesian, Arabic, or English in school and daily life. However, pesantren (Islamic boarding schools) still play an important role in keeping the Madurese language alive. This study examines how santri (students) at Pesantren Al-Hikam, Bangkalan maintain the Madurese language by looking at their opinions, challenges, and solutions. The research used a qualitative method with questionnaires (75 students) and interviews with six santri and two ustadzah (female religious teachers). The analysis was supported by theories of language attitude (Holmes, 2013), domains of use and language maintenance (Fishman, 1991; 1997), diglossia (Berger, 1990), and social networks (Milroy, 1992). Results show that santri are proud to use Madurese and see it as part of their identity. They use it in family, friendship, and religious settings, but face problems with polite speech levels like engghi bhunten (high speech level means yes-no), peer pressure, and the lower prestige of Madurese compared to other languages. To solve this, pesantren rules, peer support, and personal efforts help them keep using Madurese. The study shows that pesantren are not only for religion and education but also help protect local language and culture.